2006
DOI: 10.1093/bja/ael025
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled cervical epidural fentanyl compared with patient-controlled i.v. fentanyl for pain after pharyngolaryngeal surgery

Abstract: The study results show that cervical epidural analgesia provides marginally better pain relief at rest with no decrease in the fentanyl consumption. The use of the cervical epidural administration of fentanyl is questionable because of the possible complications of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…6,7 In our institution, we have been resorting to cervical epidural in laryngeal and hypopharyngeal surgery because it provides efficient operative anesthesia and postoperative analgesia. 8 We sought to determine if this technique was an independent prognostic factor associated with improved cancer-free survival in laryngeal and hypopharyngeal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In our institution, we have been resorting to cervical epidural in laryngeal and hypopharyngeal surgery because it provides efficient operative anesthesia and postoperative analgesia. 8 We sought to determine if this technique was an independent prognostic factor associated with improved cancer-free survival in laryngeal and hypopharyngeal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of 13 studies were conducted in European countries [39-42,46] and 4 in the United States and Canada [27,38,47,48], two in India [43,44] and one further publication enrolled patients from Europe and Israel [45]. …”
Section: Resultsmentioning
confidence: 99%
“…These benefits included pain control, however this difference did not reach statistical significance in either study (P = 0.24 and P = 0.25). Roussier et al [42] showed that mean VAS pain score at two and six hours after surgery was lower in the epidural Fentanyl group compared to the intravenous (IV) Fentanyl group. Singhal et al [44] demonstrated that epidural Morphine provided better analgesia than IV Morphine with P < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…PCA allows patients to control their own pain as small predetermined doses of analgesic medication within the limits prescribed by their physician, resulting in pain relief and patient satisfaction 3,4 . Fentanyl is frequently preferred because of its high lipid solubility resulting in rapid onset of analgesia, low incidence of sideeffects and low risk of delayed respiratory depression 5 . Tramadol also provides effective analgesia and has a low risk of respiratory depression 6 .…”
Section: Introductionmentioning
confidence: 99%